2017
DOI: 10.3389/fpls.2017.01466
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genetic Basis on Synergistic Interactions between Root Architecture and Biological Nitrogen Fixation in Soybean

Abstract: Soybean [Glycine max (L.) Merr] is an important legume crop and its yield largely depends on root architecture (RA) and biological nitrogen fixation (BNF). However, the relationship between RA and BNF, and its genetics behind remain unclear. Here, two soybean genotypes contrasting in RA and their 175 F9:11 recombinant inbred lines (RILs) were evaluated in field. The shallow-root parent, JD12, had better nodulation and higher yield than the deep-root parent, NF58. Strong correlations between shoot dry weight (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 75 publications
4
53
1
1
Order By: Relevance
“…In 2 years of field trials, both CPCoA and ANOSIM results suggest that soybean genotypes significantly influence the structure and composition of bacterial communities (Figure 2). Although we have not yet identified the genes responsible for the control of nodulation in soybean, nodulation traits are indeed determined by the genetic traits of Yang, Zhao, et al (2017), who found that three BNF QTLs could explain over 30% of the variation in soybean nodulation traits. Interestingly, the three high nodulation RILs studied herein carried at least two of the three BNF QTLs, whereas the three low nodulation RILs did not carry any of the three BNF QTLs ( Figure S1).…”
Section: Rhizobium Inoculation Changes the Co-occurrence Network Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…In 2 years of field trials, both CPCoA and ANOSIM results suggest that soybean genotypes significantly influence the structure and composition of bacterial communities (Figure 2). Although we have not yet identified the genes responsible for the control of nodulation in soybean, nodulation traits are indeed determined by the genetic traits of Yang, Zhao, et al (2017), who found that three BNF QTLs could explain over 30% of the variation in soybean nodulation traits. Interestingly, the three high nodulation RILs studied herein carried at least two of the three BNF QTLs, whereas the three low nodulation RILs did not carry any of the three BNF QTLs ( Figure S1).…”
Section: Rhizobium Inoculation Changes the Co-occurrence Network Ofmentioning
confidence: 93%
“…Two soybean cultivars (P1: low nodulation and P2: high nodulation) contrasting in nodulation and a previously identified set of six RILs with high‐nodulation (HN1–3) and low‐nodulation (LN1–3) phenotypes (Yang et al, ) were included in this study. The rhizobia used for inoculation were previously isolated from soybean nodules (Chen et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Two soybean cultivars contrasting in nodulation (P1, Low nodulation; P2, high nodulation), together with eight of their F 9:11 recombinant inbred lines (RILs; HN1-4, four lines with high nodulation; LN1-4, four lines with low nodulation) were tested. The RIL lines were selected based on nodule number and the presence (HN) or absence (LN) of at least two QTLs responsible for biological nitrogen fixation (BNF) (Supplementary Figure S1 and Supplementary Table S8; Yang et al, 2017). Field trials were conducted from June to October in 2016 and 2017 on the experimental farm (E114.48 • , N38.03 • ) of the Institute of Cereal and Oil crops, Shijiazhuang City, Heibei Province, China.…”
Section: Plant Materials and Field Trialsmentioning
confidence: 99%
“…Besides, the Bradyrhizobium spp. strains have been used to identified the QTLs responsible for BNF (Yang et al, 2017).…”
Section: Plant Materials and Field Trialsmentioning
confidence: 99%
See 1 more Smart Citation